Automated Vacuum Cleaner Robotic System - Zakaria, Adam Danial; Abdullah, Siti Nursyakinah Maisarah; Mohd Yusof, Ardiny Hamidah; Md Som, Ts Mohamad (Multidisciplinary Applied Research and Innovation, 2022)
In today’s society, every human living in the family is preoccupied with their jobs and may not have enough time to clean the house. This project presents the outcomes of developing an autonomous intelligent robot vacuum cleaner based on some new concepts in this field during the previous semester approaching artificial life like time management and workability. Other work is based on designing and analyzing some code and sensors for the development of the Internet of Things (IoT) using innovative technology, including smartphones. To bottom-up methodologies were used to design the entire vacuum robot, from the robot’s structure to the sensors and electronic components to the software pairing with hardware design procedure, including the proposed design or blueprint. The development of the robot begins with the creation of a simple and effective chassis for the robot, where the robot’s body used the electronics parts such as the microcontroller, motor drivers, wheels, and other electronic components on the robot. Then this is followed by the assembly of the components, which includes testing and calibrating the prototype. Its purpose is to make the robot affordable and feasible for the middle-class society. For instance, the developed robot will be helpful in residential applications as well as industries. This aids in keeping the workspace and house clean without the need for physical labor, and also using our gadgets like smartphones will clean the room with a single button press for the convenience of the device itself [1].